Pengaruh Struktur Modal, Keputusan Investasi, dan Profitabilitas terhadap Nilai Perusahaan pada Perusahaan Manufaktur yang Terdaftar di BEI Periode 2019-2022 - Sari, Kartika Wiratna; Sudarsi, Sri (Universitas Batanghari, 2024)
This study aims to determine the effect of capital structure, investment decisions, and profitability on firm value. The method used in this research is to use a quantitative approach. The population in this study were all manufacturing companies listed on the IDX in the 2019-2022 period. Sampling using purposive sampling method with the acquisition of the number of samples in the study was 154 samples of companies during the 2019-2022 period. The data analysis technique in this study used multiple linear regression with the help of SPSS. The results of the study indicate that capital structure (DER) has no effect on firm value, investment decisions (PER) have a positive and significant effect on firm value, and profitability (ROE) has a positive and significant effect on firm value.